PERFORMANCE DISORDERS AND QUALITY OF LIFE OF ALBANIAN CHILDREN AND ADOLESCENTS WITH CHRONIC KIDNEY DISEASE - Diamant Shtiza; Enkelejda Shkurti (European Scientific Journal, ESJ, 2013)
It has been noticed that the interest in the Quality of Life (QOL) of children and adolescent with chronic kidney disease (CKD) in Albania is increasing rapidly. Thus, the aim of this study is to investigate the prevalence of performance disorders and to evaluate the Health-Related QOL (HRQOL) in 130 patients with CKD. To appraise the prevalence of performance disorders and analyze HRQOL, we used the Strengths and Difficulties Questionnaire (SDQ) and Pediatric Inventory of Quality of Life (PedsQL) Core scales as the measuring instruments for both the children and their parents. The CKD group has lower results in nearly all areas of PedsQL. Only the lack of religion was related in a significant way with a lower global HRQOL result (OR= 5.8; P= 0.07). Furthermore, only two factors were related with a lower HRQOL result between the parents: children’s age >10 years (OR = 4.9, P=0.026) and the lack of religion (OR= 2.8, P= 0.025). The CKD group showed a higher ratio of performance and emotional disorders in all SDQ fields. Therefore, our results recommend the significance of assessing performance and social impacts of CKD in order to improve the life quality of this pediatric population.